تاثير بعض مركبات الازو لحامض السلفانيلك المتجانسة و الغير المتجانسة في معايير الدم الفسلجية والتغيرات النسجية المرضية للجرذ الابيض ودورها في حماية حاصلي الذرة الصفراء و الماش من الاصابة بفطري Rhizoctonia solani وspp Fusarium. - رضا, جمال محمد; محمد, حسين جاسم; محسن, عذراء حرجان (Al-Nahrain Journal of Science, 2018)
This study involved the preparation of some azo compounds Selphinlic acid homogeneous and heterogeneous, and to test the ability of fungi as antibiotic of these compounds in rats of these compounds prepared included Selphinlic azo imedazole , Selphinlic azo antipyerine , Selphinlic azo 5-hydroxy benzoamide and efficiency in the inhibition of radial growth of. Rhizoctonia solani& Fusarium spp in the culture media when used concentrations (4,2,1) ml of the compound / Litter of culture media. The results of the evaluation field has results showed that the compound Selphinlic azo antipyerine was more effective in improving germination percentage in the grain of maize was treated compound chemical Selphinlic azo antipyerine & R. solani as the percentage of germination to 90% compared to the transactions Selphinlic azo imedazole and Selphinlic azo amide since the rate of germination to 80 and 82%, on the other hand, there were no significant differences in the rates of germination percentage in seeds of Vigna treatment compounds Selphinlic azo imedazole and Selphinlic azo antipyerine and Selphinlic azo amide and R. solani separately since the rate of germination to (92, 90, 89%). The seeds of Vigna treatment with Fusarium and above compounds and treatment outperformed the compound Selphinlic azo amide increased the percentage of germination rate to 92%. In addition to, that all compound used in the study with good results in reducing the rate of seedling death (20, 10, 18 %) of the plants of maize treatment R. solani and compound Selphinlic azo imedazole , Selphinlic azo antipyerine and Selphinlic azo amide respectively. The maize plants treated with Fusarium and compound above had decreased rates of seedling death rate to (20, 18, 11)%. Found that while the composite Selphinlic azo imedazole was effective in reducing the death rate of seedling of Vigna seed that treated with R. solani, reaching 8% compared to transactions Selphinlic azo antipyerine and Selphinlic azo amide as the rate of seedling death rate to 10 and 11% respectivelywhile The seeds of Vigna that treated with Fusarium reduced the rates of seedling death rate of 8% at treatment of Selphinlic azo amide. Also found that these compounds may have influenced the increase the height of plants used in the study. On the other hand, results showed no significant differences in the rates of deposition of red blood cells( ESR) as they hit 2.9 and 2.8 and 2.8 mm / hour, the values of either Heamoglobin (Hb) was slightly significant difference emerged when the boat Selphinlic azo imedazole reaching 7.8 mg / L Transactions Selphinlic azo antipyerine and Selphinlic azo amide reached values of 13.2 and 13.5 mg / L respectively. The total white blood cell (WBC) has dropped significantly to 2633 and 2624 and 2526 cell / mm3 while the total number in the treatment of control cell 3550 / mm3. The results showed microscopic diagnosis of histological sections taken from the livers and kidneys of rats were studied Treated with above compounds no change in the cells of patients with tissue of organic liver and kidneys. In addition to the absence of any indicators satisfactory. And the lack of local studies on the effect of azo compounds on certain criteria for the histological and physiological rats and its role in the protection of of the Yield maize and Vigna from injury withfungi that causes rot and death of seedling infection This study was conducted which included:1 - The preparation of some azo compounds Selphinlic acid homogeneous and non homogeneous.2 - Test the ability of these compounds on certain fungi that cause rot and death of seedling and its ability to stimulate the ability of these seedling to germinate. 3 - Test the toxicity of these compounds on some physiological and histological & haematological of the Rats.